2015
DOI: 10.1016/j.jchf.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem Treatment for Pre-Clinical Hypertrophic Cardiomyopathy Sarcomere Mutation Carriers

Abstract: Background Hypertrophic cardiomyopathy (HCM) is caused by sarcomere mutations and characterized by left ventricular hypertrophy (LVH) with increased risk of heart failure and sudden death. HCM typically cannot be diagnosed early in life, although subtle phenotypes are present. Animal studies indicate alterations in intracellular calcium handling before LVH develops. Furthermore, early treatment with diltiazem appeared to attenuate disease emergence. Objectives To assess the safety, feasibility, and effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 28 publications
4
107
0
4
Order By: Relevance
“…Identification of HCM leads to lifestyle modifications, periodic SCD risk stratification, and close clinical follow-up, with the opportunity to implant an ICD for primary prevention and timely referral for septal reduction therapy. In the future, early disease identification might lead to novel therapies to prevent hypertrophy 32 or delay progression to advanced disease stages. 33 In this study, the clinical phenotypes of FG+ carriers showed substantial variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of HCM leads to lifestyle modifications, periodic SCD risk stratification, and close clinical follow-up, with the opportunity to implant an ICD for primary prevention and timely referral for septal reduction therapy. In the future, early disease identification might lead to novel therapies to prevent hypertrophy 32 or delay progression to advanced disease stages. 33 In this study, the clinical phenotypes of FG+ carriers showed substantial variation.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of genetic testing in relatives is reassurance in case the mutation is absent. However, the identification of FG+/Ph− subjects currently has limited therapeutic and prognostic consequences because at present, no therapy is available to retard or prevent the development of HCM, 32,33 and clinical manifestation cannot be predicted. 35 Moreover, a FG+/Ph− status may have psychological and socioeconomic implications.…”
Section: Fg+/ph− Individualsmentioning
confidence: 99%
“…A pilot trial investigated whether oral diltiazem attenuated disease progression in patients with preclinical HCM and an identified genetic mutation. 95 . LV end-diastolic diameter improved towards normal in the diltiazem group but decreased further in controls…”
Section: [H1] Treatment Of Energy Depletionmentioning
confidence: 99%
“…Hypertrophic cardiomyopathy is a major cause of SCD in the adult population and young athletes, and it has been suggested that intracellular calcium handling in the heart is altered before development of LVH; in addition progression of LVH development can be attenuated by preclinical use of diltiazem (Ho et al 2015). Sudden cardiac death in heart failure with reduced EF has been well-studied, and the potential role of implantable devices and pharmacological agents to prevent SCD in heart failure patients with preserved EF have been reported (Vaduganathan et al 2016).…”
Section: Prevention and Treatmentmentioning
confidence: 99%